2010
DOI: 10.1172/jci40926
|View full text |Cite
|
Sign up to set email alerts
|

Activated regulatory T cells are the major T cell type emigrating from the skin during a cutaneous immune response in mice

Abstract: Tregs play an important role in protecting the skin from autoimmune attack. However, the extent of Treg trafficking between the skin and draining lymph nodes (DLNs) is unknown. We set out to investigate this using mice engineered to express the photoconvertible fluorescence protein Kaede, which changes from green to red when exposed to violet light. By exposing the skin of Kaede-transgenic mice to violet light, we were able to label T cells in the periphery under physiological conditions with Kaede-red and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
302
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(325 citation statements)
references
References 34 publications
17
302
2
Order By: Relevance
“…To analyze the flux of cells into the insulitic lesion, we used a NOD backcross (>13 generations) of the Kaede tg mouse line, which allows noninvasive labeling and tracking of immunocytes in vivo (19)(20)(21)(22). In these mice, all cell types express the green fluorescent form of the Kaede protein, which can be irreversibly photoconverted into a red fluorescent form by violet light (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the flux of cells into the insulitic lesion, we used a NOD backcross (>13 generations) of the Kaede tg mouse line, which allows noninvasive labeling and tracking of immunocytes in vivo (19)(20)(21)(22). In these mice, all cell types express the green fluorescent form of the Kaede protein, which can be irreversibly photoconverted into a red fluorescent form by violet light (29).…”
Section: Resultsmentioning
confidence: 99%
“…We used the Kaede/NOD transgenic (tg) mouse, which expresses ubiquitously the photoconvertible fluorescent protein Kaede (19)(20)(21)(22). We tracked cell movement from a known point of "labeling"-namely, s.c. lymph nodes (LNs), into the pancreas tissue itself, which allowed us to define the kinetics of entry for lymphoid and myeloid cells, much of which turned out to be independent of antigenic specificity.…”
mentioning
confidence: 99%
“…These altered kinetics suggested that inflammation during the second challenge was being limited by more active immune regulation. Given that Tregs have been shown to be capable of limiting CS responses (42)(43)(44), this raised the possibility that Tregs contribute to the accelerated resolution of inflammation during the second challenge. To understand the contribution of Tregs in this response, we therefore examined the time course of Treg accumulation in the two-challenge CS model.…”
Section: Infiltration Of Tregs Increases Progressively In Multiple Chmentioning
confidence: 99%
“…Murine contact hypersensitivity (CHS) is a frequently used animal models of ACD (2). Recent evidences show that Foxp3 + regulatory T cells (Tregs) play essential roles in the regulation of various immune responses including CHS (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%